2010
DOI: 10.1002/cbic.201000200
|View full text |Cite
|
Sign up to set email alerts
|

Pacidamycin Biosynthesis: Identification and Heterologous Expression of the First Uridyl Peptide Antibiotic Gene Cluster

Abstract: The pacidamycins are antimicrobial nucleoside antibiotics produced by Streptomyces coeruleorubidus that inhibit translocase I, an essential bacterial enzyme yet to be clinically targeted. The novel pacidamycin scaffold is composed of a pseudopeptide backbone linked by a unique exocyclic enamide to an atypical 3'-deoxyuridine nucleoside. In addition, the peptidyl chain undergoes a double inversion caused by the incorporation of a diamino acid residue and a rare internal ureido moiety. The pacidamycin gene clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 58 publications
(69 reference statements)
0
76
0
Order By: Relevance
“…In summary, the in vivo gene disruption experiments unambiguously verified that the identified gene cluster from S. coeruleorubidus genome is directly involved in the biosynthesis of pacidamycins. Independently, Rackham et al have shown that heterologous expression of this gene cluster in Streptomyces lividans yielded pacidamycin D and a related variant, providing a parallel in vivo identification of the cluster, but they did not report any in vitro studies (18). In contrast, we studied the activity of seven encoded enzymes that allowed the assignment of their functions in the biosynthesis of pacidamycins.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In summary, the in vivo gene disruption experiments unambiguously verified that the identified gene cluster from S. coeruleorubidus genome is directly involved in the biosynthesis of pacidamycins. Independently, Rackham et al have shown that heterologous expression of this gene cluster in Streptomyces lividans yielded pacidamycin D and a related variant, providing a parallel in vivo identification of the cluster, but they did not report any in vitro studies (18). In contrast, we studied the activity of seven encoded enzymes that allowed the assignment of their functions in the biosynthesis of pacidamycins.…”
Section: Resultsmentioning
confidence: 96%
“…The identity of the cluster has been confirmed by both genetic and biochemical characterizations. After completion of this study, a parallel effort in S. coeruleorubidus genome sequencing has independently identified the same 22 gene cluster (18).…”
mentioning
confidence: 98%
“…Two new series of peptidyl-uridines whose structures are based upon mureidomycin A and tunicamycin have been synthesised as inhibitors of C. jejuni PglC, and selected compounds show IC50 values in the range 40-250 µM [35]. The biosynthetic pathway to both the pacidamycin [36][37][38] and caprazamycin [39] antibiotics has been elucidated, hence the use of biosynthetic engineering offers the possibility of generating modified uridyl peptide antibiotics via fermentation in the future. shown that mureidomycin A and liposidomycin B are both slow-binding inhibitors, while tunicamycin is a reversible inhibitor [40,41].…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 99%
“…Some cryptic gene clusters have been activated by changing growth conditions or by overproduction of transcriptional activators (Sherlach and Hertweck, 2009;Laureti et al, 2011). Genome sequences are also valuable for unravelling new biosynthetic pathways (Rackham et al, 2010), and for metabolic engineering to increase yields of specific secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%